NIAT BERKUNJUNG KEMBALI WEBSITE RSUD Dr. MOEWARDI - Wirmaningsih, Maya Aprian; Setyawan, Didik; Noor, Finisha Mahaesti (Fakultas Ekonomi - Universitas Setia Budi, 2019)
The result has purpose to test the will to revisit website of RSUD Dr. Moewardi to patient or their family. It because of the differentiation research object which gives effect to variable usage researched (Udo et al, 2011). The data analysis and hypotheses test in this research uses Structural Equation Model (SEM). Total sample of this research is 200 samples. The result research shows all hypotheses support. The result means high index of satisfaction felt by user of hospital website service has given affect to the will revisiting caused by high hope and the work hope of website service and also social affect from the environment.